Pengembangan Social Entertainment Metaverse: Pataland di Startup Cube Studio Berbasis Platform Virtual Reality - Jauhari, Alif Kamal; Roedavan, Rickman; Eriyadi, Mindit (eProceedings of Applied Science, 2024)
Cube Studio is a startup that was founded in 2020 and developed into PT Ruang Teknologi Ilmu Nusantara in 2021. As an innovative response to the COVID-19 pandemic, ViraExpoir was created which adapted the virtual exhibition concept. Seeing its potential, Surge Indonesia proposed a collaboration to develop PataLand, a social entertainment metaverse that focuses on virtual concerts. Venue and location constraints at conventional concerts often limit the number of spectators who attend. To solve this problem, Cube Studio and Surge developed PataLand with multi-platform capabilities. PataLand offers exclusive features such as direct fan-artist communication and merchandise sales. Immersive 3D environments, and gamification elements ensure fun and engaging interactions in PataLand. Moreover, the virtual reality version provides a more immersive and interactive experience for users. During the first six months, the virtual reality version of PataLand was played by 490 users with an average monthly user of 26 people. Cube Studio is expected to be able to formulate more effective marketing strategies and develop features that suit user needs, especially on the VR platform. Keywords— Cross Platform, Game, Concert, Metaverse, Virtual Exhibition